Spin transport in quantum d-dimensional XY model. (June 2019) - Lima, L.S.
Abstract: The interplay between quantum phase transition and spin transport is analyzed in the spin-1 d -dimensional ( d = 1, 2) XY chain bilayer and with a single ion anisotropy at T = 0. The model presents exchange interactions J 1, J 2 and J ⊥ . We have calculated the AC spin conductivity for this model and verified its behavior with the critical anisotropy D c and parameter α = J 2 ∕ J 1 . The effect of the sudden change in the graphic D c vs. α when D c → 0 on spin conductivity is verified. Since our results show a sudden variation of spin conductivity in region where D c → 0, we have gotten an influence of the quantum phase transition on the spin transport. We also calculate the quadrupole structure factor for the model that can be directly measured by polarized inelastic light scattering experiments. Highlights: The spin current operator and the spin conductivity have been calculated using Kubo formalism. The interplay between the behavior Dc vs α and spin transport has been analized. The quantum phase diagram (QPT) of the model has been described.